Graphene/PANI Electrode Material Characterization for Supercapacitor Application. (2020) - George, Divya; James, Georgekutty; Manjally, Jakson K.; Thomas, Joseph; Shine Kuriakose, Maria; Aryamol, K.S.; Benny, Anish; george, Soney C.
Abstract: The increment in demand for specialized energy devices is leading researchers to produce energy storage systems with high efficiency at lower cost. Supercapacitors serve as a promising candidate for this purpose. In order to achieve high capacitance composite materials of carbon and conductive polymers can be used for the fabrication of supercapacitors. Graphene can serve as a key material for the composition of high performance energy storage device with excellent energy and power densities. Graphene having high conductivity, great mechanical strength and large specific surface area serves as a promising material for supercapacitor fabrication. Polyaniline (PANI) is one of the most attractive materials for supercapacitors. To enhance the electrolyte diffusion and improve the electrochemical performance of the electrode the well-designed morphology of PANI is required. They have controllable resistance over a wide range, cost-effectiveness, high conductivity, light weight, flexibility and excellent electrochemical properties. Combination of PANI and reduced graphene oxide (rGO) results in a high-performance supercapacitor. They can serve as an alternative to rechargeable batteries for high power delivery applications. The electrically conductive rGO/PANI composites are characterized by Raman spectroscopy, FTIR, and XRD characterization. The results show that PANI is well coated over rGO using in-situ polymerisation technique, therefore improving the conductivity of the material. This composite can then be used as a supercapacitor electrode material delivering high specific capacitance.